Daratumumab and dexamethasone is safe and effective for triple refractory myeloma patients: final results of the IFM 2014‐04 (Etoile du Nord) trial. (19th June 2019) - Boyle, Eileen M.; Leleu, Xavier; Petillon, Marie‐Odile; Karlin, Lionel; Doyen, Chantal; Demarquette, Hélène; Royer, Bruno; Macro, Margaret; Moreau, Philippe; Fostier, Karel; Marie‐Lorraine, Chretien; Zarnitsky, Charles; et al.
Summary: Single agent daratumumab has shown clinical activity in relapsed, refractory multiple myeloma (RRMM). The Intergroupe Francophone du Myélome 2014‐04 trial was designed to further investigate daratumumab in combination with dexamethasone in triple RRMM patients. Patients received daratumumab infusions in combination with weekly dexamethasone until disease progression or unacceptable toxicity. Fifty‐seven patients were included in the trial and evaluable for response. The overall response rate and the clinical benefit rate were 33% ( n  = 19) and 48% ( n  = 27), respectively. Five (8·8%) patients achieved a very good partial response or better. The median time to response was 4 weeks. For responding patients, the median progression‐free survival was 6·6 months, compared to 3·7 months (3·0–5·5) for those with a minimal or stable disease. The median overall survival (OS) for all patients was 16·7 months (11·2–24·0). For responding patients, the median OS was 23·23 months, whereas that of patients with progressive disease was 2·97 months. The incidence of infusion‐related reactions was 37%; all cases were manageable and did not lead to dose reduction or permanent treatment discontinuation. These data demonstrate that treatment with daratumumab and dexamethasone results in a meaningful long‐term benefit with an acceptable safety profile for patients with triple RRMM.